Feedback inhibition of adrenocorticotropic hormone by physiological increases in plasma corticosteroids in conscious dogs. - M E Keller-Wood; J Shinsako; M F Dallman (The Journal of Clinical Investigation, 1983)
We have tested the effect of physiological increases in plasma corticosteroids in conscious dogs on the levels of basal and hypoglycemia-stimulated adrenocorticotropic hormone (ACTH) 2 h later. Increases in plasma corticosteroids, produced by infusion of alpha-1-24 ACTH or corticosteroids for 40 min, suppressed basal and stimulated ACTH levels. The magnitude of inhibition produced by an increase in plasma corticosteroids induced by the infusion of ACTH was equivalent to the inhibition produced by the same increase in plasma corticosteroids induced by corticosteroid infusion. The infusions did not affect basal plasma glucose concentrations or the decrease in plasma glucose concentrations after administration of 0.1 U insulin/kg. Basal ACTH concentration was less sensitive than hypoglycemia-stimulated ACTH concentration to corticosteroid-induced suppression. Basal and stimulated secretion were significantly inhibited in all dogs after approximately half-maximal increases in plasma corticosteroids; maximum inhibition occurred after maximal increases in plasma corticosteroids. Therefore, physiological increments in plasma corticosteroids, similar to those produced by acute stress, are effective suppressors of subsequent stress-induced ACTH secretion. Images